Relationship between mechanical effectiveness in sprint running and force-velocity characteristics of a countermovement jump in Australian rules football athletes - Morris, C. G.; Weber, J. A.; Netto, K. J. (The Journal of Strength and Conditioning Research, 2022)
This study evaluated the mechanical determinants of 40-m sprint performance in elite Australian Rules Football (ARF) athletes and identified variables of countermovement jumps (CMJs) that related to the sprint. Fourteen elite male ARF athletes (age = 22.7 ± 3.6 years; height = 1.88 ± 0.08 m; mass = 88.2 ± 9.38 kg) completed two 40-m sprints and 3 CMJs. Sprint mechanics were calculated using inverse dynamic methods from sprint times, anthropometric and spatiotemporal data, whereas CMJ variables were obtained from in-ground force plates. Associations between sprint mechanics, sprint performance, and CMJ variables were identified using Pearson's correlation coefficient. A p-value of <0.036 was considered statistically significant for all analyses after performing Bonferroni correction adjustment. Relative peak running power was significantly correlated (p < 0.036, r = -0.781 to -0.983) with sprint split times across all distances (5-40 m). Relative maximum horizontal force significantly correlated with acceleration performance (0-20 m, p < 0.036, r = -0.887 to -0.989). Maximum running velocity was significantly correlated (p < 0.036, r = -0.714 to -0.970) with sprint times across 20-40 m. Relative peak force in the CMJ was significantly associated (p < 0.036, r = -0.589 to -0.630) with sprint kinetics (power and horizontal force) and 5-20-m sprint times. Jump height and concentric time in the CMJ were significantly (p < 0.036) correlated with sprint time at 20 m (r = -0.550 and r = 0.546), respectively. These results indicate emphasis should be placed on training protocols that improve relative peak power, particularly in time-constrained environments such as team sports, focusing on maximal force production or maximal running velocity ability. Furthermore, associations between CMJ variables and sprint performance provide practitioners with an approach to assess sprint performance in-season, monitor training adaptations and further individualize training interventions, without requiring maximal sprint testing.